Preparation Of Microwave-Assisted Palm Trunk Based Activated Carbon For Adsorption Of Methylene Blue Dye - Latif, Mohd Shafiq Abd (Universiti Sains Malaysia, 2017)
In this study, the adsorption process by the palm trunk based activated carbon was investigated in batch process at various initial dye concentration (25-300 mg/L), contact time (0-24 hours) and solution temperature (30-60 ⁰C). The PTAC was prepared by physical activation which involve microwave radiation and carbon dioxide (CO2) gasification were applied. The optimum PTAC preparations obtained from response surface methodology (RSM) were at radiation power and activation time of 501 W and 4.00 minutes, respectively. This sample has 91.25% MB dye removal and 32.37% PTAC yield. This sample has 772.35 m2/g BET surface area, 0.45 cm3/g pore volume and 74.3% fixed carbon content. The pores developed were mesopores type which have 3.88 nm average pore size diameter. The adsorption isotherm was fitted with Freundlich model while the kinetics data was best represented by the pseudo first-order model. The adsorption process of MB onto PTAC was endothermic and spontaneous.